Slope displacement patterns observed using satellite InSAR data in the Storfjord-Kåfjord-Lyngen region, Troms - Eriksen, Harald Øverli (Universitetet i Tromsø, 2013)
Norway is particularly susceptible to large rockslides due to its many fjords and steep mountains. One of the most dangerous hazards related to rock slope failures are tsunamis that can lead to large loss of life. Many rockslides are clustered east of the Storfjord and Lyngen fjord in Troms county, northern Norway, where several mapped unstable rock slopes occur within the zone of sporadic permafrost. Among these, the Nordnes rockslide has been classified as high-risk due to the severe consequences should catastrophic failure occur. In order to fully understand the kinematics and geometric configurations susceptible for sliding, it is imperative to obtain precise measurements of the stability of potential unstable rock slopes. Multi-temporal satellite interferometric synthetic aperture radar (InSAR) techniques involve comparing the phase information from multiple spaceborne SAR images, produced at different times, to detect millimeter to centimeter scale ground deformation patterns. However, the satellite radar is only capable of measuring displacement that has a component in the radar line-of-sight (LOS). By combining InSAR data acquired in both ascending and descending orbits, it is possible to extract more information about the true displacement vector, increasing the interpretability of the displacement patterns. In this thesis, multi-temporal InSAR methods are applied to an extensive time series of TerraSAR-X data collected in both ascending and descending geometries during the summer seasons in the period 2009-2012. The estimated deformation rates from the ascending and descending geometries are decomposed into 2D InSAR data consisting of deformation in the vertical and east/west directions, dip angle and total displacement. The computed 2D InSAR displacement data are validated with GPS data from the Nordnes rockslide. For the study area, the 2D InSAR are related to geomorphological- and structural elements in different slope processes; a rock glacier, solifluction tongues, a fast moving rockslide ...